Microchannel Heat Sinks For Cooling High Heat Flux Electronic Devices―analysis With Single And Two Phase Flows - Hegde, Pradeep Ganesh (2006)
Microchannel heat sinks constitute an innovative cooling technology for the efficient dissipation of the large amounts of heat from the very small and constrained areas of the high heat flux microelectronic chips and circuits.